O filme como kukràdjà: o fazer cinema dos mebêngôkre-kayapó da aldeia A'ukre - Lima, Amilton Rosa de (2022)
Since the beginning of contact between whites and Amerindians, there has been an exchange of artifacts: agriculture and fishing materials, kitchen utensils, household appliances, as well as audiovisual equipment. The possibility of registering, as a historical document to record memories, or to disseminate images of their customs to other indigenous groups, as a political document, used as evidence about the promises made to the authorities, attests to its potential for use. From this interest, a vast indigenous film production was consolidated and this work explores this filmmaking, focusing on the production of the mebêngôkre-kayapó A’Ukre village, also paying attention to the agents who participate in this construction. For this purpose, the film production process of the village filmmakers was studied, analyzing the films they made, at a time of notorious consolidation of this production in the village, when a media center was being built in its territory, as well as workshops for the training of new indigenous filmmakers. Films prior to a workshop held by members linked to the “Vídeo nas aldeias” project were analyzed, as well as the images produced during this workshop, seeking to capture aesthetic choices and transformations between these two moments, in addition to the relationship of these choices with the Mebêngôkre sociocosmological regime.